Exploring medical students’ perceptions on the effectiveness of a clinical skills rotation at a clinical skills laboratory - Rahim, Muhammad Faisal (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMed)--Stellenbosch University, 2018.